2015
DOI: 10.1371/journal.pcbi.1004224
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Gene Expression Space of Individual Cells

Abstract: There is a revolution in the ability to analyze gene expression of single cells in a tissue. To understand this data we must comprehend how cells are distributed in a high-dimensional gene expression space. One open question is whether cell types form discrete clusters or whether gene expression forms a continuum of states. If such a continuum exists, what is its geometry? Recent theory on evolutionary trade-offs suggests that cells that need to perform multiple tasks are arranged in a polygon or polyhedron (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 97 publications
1
85
0
Order By: Relevance
“…It is an unsupervised method, since the algorithm is given only the raw data, not any descriptive or outcome-related information (e.g., diagnoses). It has been used in a wide variety of fields, including sports analytics (33), astrophysics (34), marketing (35), and bioinformatics/medicine (16,36,37). Although it is common to show archetype results on a PCA plot as we do here, AA is conceptually very different from PCA.…”
Section: Methodsmentioning
confidence: 99%
“…It is an unsupervised method, since the algorithm is given only the raw data, not any descriptive or outcome-related information (e.g., diagnoses). It has been used in a wide variety of fields, including sports analytics (33), astrophysics (34), marketing (35), and bioinformatics/medicine (16,36,37). Although it is common to show archetype results on a PCA plot as we do here, AA is conceptually very different from PCA.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis of such models also showed that branches and bifurcations of states occur naturally in the context of cell cycle modelling (Noel et al, 2012). In a more general context, geometric analysis of single-cell expression data from human and mouse tissues showed that gene expression is structured in clusters but also in continua of states within polyhedra whose vertices can be understood as specialized key tasks (Korem et al, 2015). These findings were interpreted in terms of multi-objective optimization solutions (Korem et al, 2015), but could also suggest transient behaviour between specialized states.…”
Section: Introductionmentioning
confidence: 63%
“…The functional identity of each cell is closely associated with its underlying type [3] and a number of methods have been proposed to directly identify cell types from the transcriptional profiles of single cells [4][5][6][7][8][9]. A majority of these methods rely on classic measures of distance between transcriptional profiles to establish cell types and their relationships.…”
mentioning
confidence: 99%
“…To validate cell types identified using ACTION, we compare our method to four recently proposed methods: SCUBA [5], SNNCliq [7], single-cell ParTI [8,13], and TSCAN [9] (see Supplementary Text 1 for a brief description of these methods) to predict annotated cell types on the same four datasets (see Methods, Component 2). All methods (including ACTION) have no user-configurable parameters -except for SNNCliq.…”
mentioning
confidence: 99%
See 1 more Smart Citation